Monitoring the Corrosion of Steel in Concrete Exposed to a Marine Environment - Gartner, Nina (Materials (Basel), 2020)
Reinforced concrete structures require continuous monitoring and maintenance to prevent corrosion of the carbon steel reinforcement. In this work, concrete columns with carbon and stainless steel reinforcements were exposed to a real marine environment. In order to monitor the corrosion processes, two types of corrosion probes were embedded in these columns at different height levels. The results from the monitoring of the probes were compared to the actual corrosion damage in the different exposure zones. Electrical resistance (ER) probes and coupled multi-electrodes (CMEs) were shown to be promising methods for long-term corrosion monitoring in concrete. Correlations between the different exposure zones and the corrosion processes of the steel in the concrete were found. Macrocell corrosion properties and the distribution of the separated anodic/cathodic places on the steel in chloride-contaminated concrete were addressed as two of the key issues for understanding the corrosion mechanisms in such environments. The specific advantages and limitations of the tested measuring techniques for long-term corrosion monitoring were also indicated. The results of the measurements and the corrosion damage evaluation clearly confirmed that the tested stainless steels (AISI 304 and AISI 304L) in a chloride-contaminated environment behave significantly better than ordinary carbon steel, with corrosion rates from 110× to 9500× lower in the most severe (tidal) exposure conditions.